A qualitative case study on the use of balance scorecard to control performance of a local government-owned water supply company in Indonesia - Praptapa, Agung; Yahya, Mohd Azlan; Sawandi, Norfaiezah (Institute for Management and Business Research (IMBRe), Universiti Utara Malaysia, 2016)
This paper discusses how the Balance Scorecard is applied in a water supply company in Indonesia. The company investigated in this study was a local government-owned water supply company is responsible for generating profit, as well as having a social function. Performance becomes an important issue in this type of company, not just from the financial aspect, but also regarding non-financial performance. This research was a longitudinal case study. By applying ethnography, the researcher participated in the process of controlling performance while performing the research, where the case company modified the four perspectives of balance scorecard into four aspects of performance, i.e., financial, service, operational, and human resource performance aspects. This modified balance scorecard was used to control people in achieving their targeted performance. A management control system model was then used as a tool and mechanism to control performance.